Adapting War Horse Cognition, the Spectator, and a Sense of Play - Malone, Toby.; Jackman, Chris; SpringerLink (Online service) (London : Palgrave Macmillan UK(Imprint), 2016)
This book analyses the success and adaptation of Michael Morpurgo's novel War Horse to stage, radio, live events, and feature film, in different cultures, on tours, and in translation. In under a decade, War Horse has gone from obscure children's novel to arguably one of the world's most recognisable theatrical brands, thanks to innovative puppet designs from South Africa's Handspring Puppet Company in an acclaimed stage production from the National Theatre of Great Britain. With emphasis on embodied spectatorship, collaborative meaning-making, and imaginative 'play,' this book generates fresh insights into the enduring popularity of the franchise's eponymous protagonist, Joey, offering the most in-depth study of War Horse to date. Toby Malone is a graduate of the University of Toronto's Graduate Centre for Study of Drama, Theatre, and Performance Studies, and is currently a faculty member at the University of Waterloo, Canada. Previous publications include Shakespeare Survey, Literature/Film Quarterly, Canadian Theatre Review, Borrowers and Lenders and The Routledge Companion to Dramaturgy. Christopher J. Jackman is a graduate of the University of Toronto's Graduate Centre for Study of Drama, Theatre, and Performance Studies, and is an alumnus of Massey College, Canada. He is currently Chair of Arts and Design at Centennial College in Toronto, has developed Centennial's performing arts certificate programme, and remains an active director and performer. .
Introduction. Playing the War Horse Game.-Chapter 1. "We Get to Know Him" -- Chapter 2. "Making Fit" -- Chapter 3. Spectatorship as Embodied Practice -- Chapter 4. Animated Horse-Play -- Chapter 5. Emotional Promises -- Chapter 6. Tour Horse -- Works Cited.
Keywords: Performing arts; Children's literature; Motion pictures-Great Britain